Perubahan Sosial Terhadap Hadirnya Pariwisata Pantai Tebing di Desa Sungai Dua Laut Kabupaten Tanah Bumbu - Ayu Yesvana Pratiwi; Dimas Asto Aji An'Amta (Huma: Jurnal Sosiologi, 2023)
Tebing Beach in Sungai Dua Laut Village is a new tourism area in Tanah Bumbu Regency, which has caused changes to occur in aspects of village community life. This study aims to see how the process of social change that occurred in Sungai Dua Laut Village towards the presence of Tebing Beach tourism. This study uses a descriptive-qualitative approach to qualitative research. Data collection techniques using non-participatory observation, in-depth interviews and documentation. This study used the data analysis technique of Miles and Huberman's interactive model, namely data collection, data reduction, data presentation and drawing conclusions. From the results of this study, it was found how the community accepted the changes that were due to the presence of the Tebing Beach tourism object. It was found that there was a new norm value applied by the people of Sungai Dua Laut Village, namely Sapta Pesona which consists of 7 elements namely safe, orderly, clean, cool, beautiful, warm-hearted, and Memories to create a harmonious atmosphere between communities. Besides that, there is a manifest function, namely conscious and planned changes such as increasing community solidarity with the establishment of Pemuda Membangun Desa (PMD), environmental care actions, non-productive land use, and community openness to new things. As well as the existence of a latent function of the Pemuda Membangun Desa (PMD) such as the concern for the community outside the Sungai Dua Laut Village area for the condition of the people of Sungai Dua Laut Village and the process of community acceptance of foreigners. Then there is a manifest concept of the rise of the Pemuda Sahabat Laut (PSL) organization which then has monitoring of the coastal and marine environment and the existence of tour guides carried out by members of Pemuda Sahabat Laut (PSL).